IMPLEMENTASI LAYANAN BIMBINGAN KELOMPOK SEBAGAI UPAYA PENINGKATAN KESEHATAN MENTAL WARGA BINAAN LAPAS KELAS III RANGKASBITUNG - Avicena; Arga Satrio Prabowo; Lenny Wahyuningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the effectiveness of group counseling services in improving the mental health of inmates at Class III Rangkasbitung Correctional Institution. Inmates are a vulnerable group who often experience psychological problems such as depression, anxiety, and stress due to loss of freedom, separation from family, and limited activities in prison. The study applied a Community-Based Participatory Research (CBPR) approach involving collaboration between researchers, officers, and inmates in identifying problems and designing interventions. A total of 26 inmates in early adulthood were selected using purposive sampling based on Depression Anxiety Stress Scale 21 (DASS-21) scores. Group counseling was implemented to facilitate emotional expression, self-awareness, and coping skills. The results showed a significant decrease in depression, anxiety, and stress levels after the intervention. Initially, several inmates were categorized into moderate and severe levels, but after the program all participants shifted into normal and mild categories. These findings indicate that group counseling creates social support, positive interaction, and constructive reflection that help inmates regulate emotions more effectively. The study concludes that group counseling is an effective psychological intervention and should be implemented continuously as part of correctional rehabilitation programs using a collaborative CBPR framework. Keywords: group counseling, mental health, inmates, DASS-21